Prevention of crime, tort and epidemy: The use of criminal procedure for preventive purposes in Poland during Covid-19 - Lach, Arkadiusz (Criminology & criminal justice, 2023)
Criminal procedure is increasingly becoming an important instrument of prevention. This is a globally observed tendency, and Poland is not an exception. There are several regulations in the Polish Code of Criminal Procedure that allow the preventive use of coercive measures. In 2020, a new and controversial regulation was introduced, authorising the public prosecutor or court to prohibit the publication of content interfering with the legally protected goods of the victim. The author criticises the new preventive measure as duplicating civil law injunctions and expresses the opinion that, in criminal procedure, preventive measures should be used to prevent crime, not every illegal activity. In addition, the article describes the criminal procedure for isolating persons obliged to quarantine themselves because they have tested positive for Covid-19 or had contact with infected persons. This raises the question of the limits of the preventive function of provisional arrest and possible abuse of the criminal process using it for aims unrelated to the traditional goal of the criminal process: determining the question of guilt of the accused.